2017
DOI: 10.1080/15389588.2017.1314470
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic injury in sub-Saharan African countries: A systematic review and summary of observational studies

Abstract: The number of studies evaluating RTI proportions and fatalities in SSA countries is increasing but without the exponential rise expected from World Health Organization calls for research during the Decade of Action for Road Traffic Injuries. Further research infrastructure including standardization of taxonomy, definitions, and data reporting measures, as well as funding, would allow for improved cross-country comparisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 78 publications
3
27
2
Order By: Relevance
“…This study revealed that the pooled prevalence of RTI among trauma patients in Ethiopian hospitals was 31.5%. This finding was comparable with a prevalence report in sub-Saharan Africa (32%) [9] and low- and middle-income countries (13% to 31%) [14] . Although low-income countries have nearly half of the world's vehicles, the majority of vehicles accident had been occurred in these countries [37] and the burden of RTI in the hospitals become still higher than the developed world.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study revealed that the pooled prevalence of RTI among trauma patients in Ethiopian hospitals was 31.5%. This finding was comparable with a prevalence report in sub-Saharan Africa (32%) [9] and low- and middle-income countries (13% to 31%) [14] . Although low-income countries have nearly half of the world's vehicles, the majority of vehicles accident had been occurred in these countries [37] and the burden of RTI in the hospitals become still higher than the developed world.…”
Section: Discussionsupporting
confidence: 90%
“…Based on 2000–2020 WHO projection, road traffic-related deaths expected to increase by 80% in low- and middle-income countries [8] . The estimated prevalence of RTI among trauma patients in sub-Sahara Africa was 32% [9] . RTI is a hidden epidemic causes of morbidity and mortality in developing countries [10] where by more than 90% of death are related with road traffic accidents [11] .…”
Section: Introductionmentioning
confidence: 99%
“…These have mostly included legislative regulations, educational interventions, law enforcement, infrastructural reform, and community-based prevention programs [ 21 ]. At the same time, a growing number of sub-Saharan African trauma registries have aimed to provide clinicians, researchers, and administrators clearer data regarding local burden of traumatic illness [ 18 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other forms of NCDs such as injuries are responsible for a significant proportion of DALYS. Injuries resulting from road accidents (motor vehicles and motor bikes) have increasingly taken a growing toll on human health [33]. Mental disorders, including depression and anxiety, or severe forms like psychosis, schizophrenia and bipolar, as well as alcohol and substance dependence are common.…”
Section: Burden and Trends Of Ncds In Africamentioning
confidence: 99%